Incongruities in Innovation: Exploring Inconsistencies in Business Innovation Strategies - Eddy Sumartono (Journal of Knowledge and Collaboration, 2024)
This research explores the phenomenon of incongruities in business innovation strategy through a systematic literature review. Analysis of the current literature reveals different types of incongruities, their causal factors, and their impact on innovation performance. Findings show that strategy-implementation gaps, culture-innovation misalignment, and resource allocation inconsistencies are the most common types of incongruities. Factors such as short-term performance pressure and resistance to change contribute significantly to the occurrence of incongruities. Their impact on innovation performance includes innovation portfolio imbalance and failure in radical innovation. Strategies to overcome incongruities include the development of ambidextrous leadership, balanced innovation portfolio management, and enhancement of organizational dynamic capabilities. This research highlights the importance of a holistic approach in innovation management and provides directions for future research.